L’objet, le musée et la main interdite - Joaquim Pais de Brito (Mélanges de la Casa de Velázquez, 2010)
In a museum, the objects are still, trapped. Contrasting with their nomadic existence on the outside —a life of use, movement and change— in the museum they are confined and sedentary the better to be identified and preserved. They can no longer be touched. Nonetheless display in a museum still leaves room for transfigurations and inquiries which, beyond the substance and the original purpose of the object, offer it the possibilities of other existences and enhancements of meaning.